A LytM-Domain Factor, ActS, Functions in Two Distinctive Peptidoglycan Hydrolytic Pathways in E. coli - Chodisetti, Pavan Kumar; Bahadur, Raj; Amrutha, R. N.; Reddy, Manjula (Frontiers in Microbiology, 2022)
Bacterial cell walls contain peptidoglycan (PG) to protect cells from turgor and environmental stress. PG consists of polymeric glycans cross-linked to each other by short peptide chains and forms an elastic mesh-like sacculus around the cytoplasmic membrane. Bacteria encode a plethora of PG hydrolytic enzymes of diverse specificity with crucial roles in growth, division, or turnover of PG. In E. coli, the cross-link specific endopeptidases, MepS, -M, and -H facilitate enlargement of PG sacculus during cell elongation whereas LytM-domain factors, EnvC and NlpD activate division-specific amidases, AmiA, -B, and -C to facilitate cell separation. In a screen to isolate additional factors involved in PG enlargement, we identified actS (encoding a LytM paralog, formerly ygeR) as its overexpression compensated the loss of elongation-specific endopeptidase, MepS. Overexpression of ActS resulted in generation of partly denuded glycan strands in PG sacculi, suggesting ActS is either an amidase or an activator of amidase(s). Detailed genetic and biochemical analyses established that ActS is not a PG hydrolase by itself, but an activator of the division-specific amidase, AmiC. However, interestingly, the suppression of the mepS growth defects by actS is not mediated through AmiC. Domain-deletion experiments confirmed the requirement of the N-terminal LysM domain of ActS for activation of AmiC, but not for alleviation of growth defects of mepS mutant indicating that ActS performs two distinctive PG metabolic functions. Altogether our results suggest that in addition to activating the division-specific amidase, AmiC, ActS modulates yet another pathway that remains to be identified.